On "free" grammatical variation in a mixed lect: Clitic placement in Cypriot Greek - Grohmann, Kleanthes K.; Kambanaros, Maria; Leivada, Evelina; Pavlou, Natalia (My University, 2021)
Variation involving a switch between pre- and post-verbal placement of pronominal object clitics in a single syntactic environment within a language is unexpected. The rationale why this would not be expected is clear: Languages pattern as either proclitic or enclitic with respect to object clitic placement, possibly allowing one or the other option across different syntactic environments. We provide an overview of our research from data collected in Cyprus, related to the development and use of pronominal object clitics for child populations and adult speakers that are bilectal in Cypriot and Standard Modern Greek. While it has been shown that the tested bilectal populations receive exposure to more than one distinct grammar, including mixed grammars with optional choices for clitic placement, an important question remains unaddressed: Is variation really "free"across all speakers or are there universally reliable predictors (such as gender, age, or level of education) that mediate a consistent use of either the standard or the dialect? Combining insights from targeted elicitation tasks administered to different groups, a corpus of spontaneous speech, and an extensive literature review, we show the weakness of such purported predictors and support a claim of free variation.
Keywords: Bilectalism; Clitic placement; Development; Optionality; Variation